Response of Gut Microbiota to Metabolite Changes Induced by Endurance Exercise - Zhao, Xia; Zhang, Zhujun; Hu, Bin; Huang, Wei; Yuan, Chao; Zou, Lingyun (Frontiers in Microbiology, 2018)
A few animal studies have shown that wheel running could reverse an unhealthy status by shifting the gut microbial composition, but no investigations have studied the effect of distance running on human gut microbial communities. Since many findings have shown that marathon running immediately causes metabolic changes in blood, urine, muscles and lymph that potentially impact the gut microbiota (GM) within several hours, here, we investigated whether the GM immediately responds to the enteric changes in amateur half-marathon runners. Alterations in the metabolic profile and microbiota were investigated in fecal samples based on an untargeted metabolomics methodology and 16S rDNA sequencing analysis. Our results demonstrated that 40 fecal metabolites related to nucleic acid components, organic acids, sugar, alcohols, steroids, lipids, and amino acid metabolites were significantly changed after finishing a half-marathon race. The most significantly different metabolites were organic acids (the major increased metabolites) and nucleic acid components (the major decreased metabolites). Eight differential metabolites were significantly enriched in the pentose phosphate pathway, in pyrimidine metabolism and in phenylalanine, tyrosine and tryptophan biosynthesis. The enteric changes induced by running did not affect the α-diversity of the GM, but the abundances of certain microbiota members were shown to be significantly different before and after half-marathon running. Correlation analysis indicated that the observed differential GM in our study might have been the shared outcome of running and diet. The family Coriobacteriaceae was identified as a potential biomarker that links exercise with health improvement. This study provided knowledge regarding the health impacts of marathon running from the perspective of GM for the first time. Our data indicated that long-distance endurance running can immediately cause striking metabolic changes in the gut environment. Gut microbes can rapidly respond to the altered fecal metabolites by adjusting certain bacterial taxa. These findings highlighted the health-promoting benefits of exercise from the perspective of GM.